The Factors That Affect Employee Creativity among Staff in a Malaysian Energy Corporation - Azman, Saidatul Nur Atieka binti; Anwar, Nur Aizureen; Hussein, Norashikin; Omar, Norhayati; Razali, Murni Zarina Mohamed (Information Management and Business Review, 2023)
This article aims to analyze the factors that affect employee creativity among staff in a Malaysian operating in the energy industry that faced the crucial situation impact of the COVID-19 pandemic. The total number of respondents involved in this study is 108 using a questionnaire as an instrument in this study. As a result of correlation analysis, it shows that there are significant relationships between personality and work environment with employee creativity. For reward, there is no relationship with employee creativity. According to the result of multiple regression, R2 was 37.6% which means all the independent variables influence the dependent variable on that amount. The rest of the amount 62.4% is influenced by other factors. The regression result also shows that only the hypothesis on personality and work environment is supported. And other factors that affect employee creativity should be considered in future research. The significance of this study is to highlight the importance of understanding the factors affecting employees’ creativity during Movement Control Order (MCO). From the perspective of the organization, this study helps to better understand its operation and to maximize employee creativity during MCO. On the other hand, the employees may benefit from this study by giving awareness, to educate and support employees during MCO as some need to Work-From-Home (WFH) with problems with internet connection.